Classificação automática de gêneros musicais em bases de letras de músicas em diferentes idiomas utilizando métodos de combinação de classificadores - Lima, Adriano Alves de (2015)
The automatic music genre classification is an important area in music information retrieval. For assist this task many languages resources of natural language processing has been used in song lyrics. This is important considering that the classification audio-based might be comple- mented with lyrics features to improve the results. This work analyzes such natural language processing tools employed to song lyrics in different languages for the music genre classi- fication. Furthermore, we studied other techniques to improve the classification results, for example, features combination by mean of early and late fusion methods. To run the experiments were created three lyrics database in various music genres into the Latin languages (Portuguese and Spanish), Nordic (Danish, Norwegian and Swedish) and En- glish. The results obtained shown that the combination approaches by mean of late fusion with product of the probability and early fusion outperformed the other approaches in music genre classification using song lyrics in different languages.